Loss of LAPTM4A inhibits M2 polarization of tumor-associated macrophages in glioblastoma, promoting immune activation and enhancing anti-PD1 therapy - Jin Geng; Bing Liang; Zonghao Zhang; Fengping Shan; Xinxin Zhao; Ye Yuan (Communications Biology)
Abstract Glioma is a highly aggressive central nervous system tumor with limited treatment options, presenting a significant challenge for effective therapy. Despite advancements, the role of tumor-associated macrophages (TAMs) in glioma remains poorly understood, especially regarding their polarization and its impact on the immune response. This study investigates the effects of Lysosomal-associated protein transmembrane 4 A (LAPTM4A) deficiency on the polarization of TAMs and its role in modulating anti-tumor immunity. Using C57BL/6 male mice, we established an orthotopic glioma model and employed single-cell RNA sequencing, flow cytometry, in vitro co-culture systems, and in vivo anti-PD-1 therapy experiments to explore the functional role of LAPTM4A. We found that LAPTM4A promotes M2 polarization of TAMs, contributing to glioma progression by enhancing cell proliferation and invasion. In contrast, LAPTM4A-deficient glioma models show a shift towards M1 macrophage phenotypes, leading to stronger immune activation and increased sensitivity to anti-PD-1 therapy. These results suggest that targeting LAPTM4A may provide a novel strategy to improve glioma treatment by modulating TAM polarization and enhancing immune responses. This research lays the groundwork for future therapies aimed at reprogramming the tumor microenvironment to combat glioblastoma.